2010
DOI: 10.1038/ki.2009.433
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure occurs in chronic lithium treatment but is uncommon

Abstract: We sought to establish the prevalence of lithium-induced end-stage renal disease in two regions of Sweden with 2.7 million inhabitants corresponding to about 30% of the Swedish population. Eighteen patients with lithium-induced end-stage renal disease were identified among the 3369 patients in the general lithium-treated population, representing a sixfold increase in prevalence compared with the general population for renal replacement therapy. All lithium-treated patients were older than 46 years at end-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
136
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(155 citation statements)
references
References 18 publications
9
136
1
9
Order By: Relevance
“…The investigators demonstrated that lithium users had a sixfold greater risk of needing renal replacement therapy compared with the general population [18]. However, the authors noted that end-stage kidney disease attributable to lithium is uncommon (only 18 patients were detected out of 3369 lithium treated patients).…”
Section: Discussionmentioning
confidence: 99%
“…The investigators demonstrated that lithium users had a sixfold greater risk of needing renal replacement therapy compared with the general population [18]. However, the authors noted that end-stage kidney disease attributable to lithium is uncommon (only 18 patients were detected out of 3369 lithium treated patients).…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence in lithium-using patients was reported as approximately 1.5%, which is six to eight times higher than in the general population. 7,67 The duration of lithium treatment is an important factor, because the vast majority of patients with ESRD were treated for .15 years with lithium. 7,67 Although a report in 2014 suggested that the less-controlled treatment regime for lithium in the 1960s and 1970s strongly contributed to the development of ESRD, a later report showed that 5% of patients who started lithium treatment after 1980 and continued for 10-29 years also displayed evidence of ESRD.…”
Section: Esrdmentioning
confidence: 99%
“…7,67 The duration of lithium treatment is an important factor, because the vast majority of patients with ESRD were treated for .15 years with lithium. 7,67 Although a report in 2014 suggested that the less-controlled treatment regime for lithium in the 1960s and 1970s strongly contributed to the development of ESRD, a later report showed that 5% of patients who started lithium treatment after 1980 and continued for 10-29 years also displayed evidence of ESRD. 6,68 Whether this treatment regime reduces the occurrence of lithium-induced ESRD compared with the practices in the 1960s and 1970s remains to be addressed.…”
Section: Esrdmentioning
confidence: 99%
See 2 more Smart Citations